2010
DOI: 10.1002/ca.20924
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic variation of the clavicle: A novel three‐dimensional study

Abstract: An understanding of the complex anatomy of the clavicle is helpful in the treatment of clavicular fractures. Using three-dimensional (3D) statistical shape analysis, the author presents a novel method to assess geometric morphology of the clavicle. Fifteen fresh frozen shoulder specimens were scanned using high-resolution computerized tomography (CT) but four were excluded from the study. A further 16 high-resolution CT scans of the clavicle were obtained by searching the hospital database. All 27 scans were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 10 publications
7
36
0
Order By: Relevance
“…This fact is also represented in the reconstruction template evaluation, by a significantly greater translation error along the X-axis (i.e., in medial-lateral direction) compared to the other axes. Consistent with our results, a significant greater length of the left clavicle was reported in the literature (Daruwalla et al, 2010;Cunningham et al, 2013;Bernat et al, 2014). A common hypothesis is the influence of hand dominance on the clavicle length because, considering that the majority of people are right handed, excessive motion of the dominant side results in increased wear of the clavicle ends over time (Daruwalla et al, 2010).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…This fact is also represented in the reconstruction template evaluation, by a significantly greater translation error along the X-axis (i.e., in medial-lateral direction) compared to the other axes. Consistent with our results, a significant greater length of the left clavicle was reported in the literature (Daruwalla et al, 2010;Cunningham et al, 2013;Bernat et al, 2014). A common hypothesis is the influence of hand dominance on the clavicle length because, considering that the majority of people are right handed, excessive motion of the dominant side results in increased wear of the clavicle ends over time (Daruwalla et al, 2010).…”
Section: Discussionsupporting
confidence: 95%
“…Consistent with our results, a significant greater length of the left clavicle was reported in the literature (Daruwalla et al, 2010;Cunningham et al, 2013;Bernat et al, 2014). A common hypothesis is the influence of hand dominance on the clavicle length because, considering that the majority of people are right handed, excessive motion of the dominant side results in increased wear of the clavicle ends over time (Daruwalla et al, 2010). Unfortunately, we were unable to correlate our findings with the handedness of our subjects as this data was unavailable.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Experience to date has shown that linear scaling is a dominant mode of variation in human anatomy [1]. This paper builds on geometric data and methodology presented in a previous study analyzing linear measurements [2] in order to provide detailed information relating to the modes of variation in three-dimensional (3D) shape that occur in the clavicle. It must be noted that while intramedullary and plate fixation are accepted and widely used methods of treatment for fractures of the clavicle, current clavicular implants overlook the variations in geometry of the bone.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have assessed the relative advantages of dissections versus prosections in medical school anatomy courses, typically concluding that cadaver dissections are a preferable way to teach future clinicians about the clinical relevance of anatomical facts and relationships (Hisley et al, 2008). Yet other studies have documented the value of innovation and reform in medical school anatomical education in the United States (Gregory et al, 2009;Hildebrandt, 2010;Sugand et al, 2010); the benefits of digital, and in some cases three-dimensional anatomy simulations to support undergraduate and postgraduate anatomy instruction (Hisley et al, 2008;Thakore and Mahon, 2008;Yip and Rajendran, 2008;Daruwalla et al, 2010), and the role of anatomy education in transmitting professional values to clinical students (Pawlina, 2006;Pearson and Hoagland, 2010). Researchers also have investigated the benefits of exploratory learning to teach clinical reasoning and to prepare anatomy students for future clinical work (Philip et al, 2008), the benefits of developing writing skills regarding anatomical knowledge as a preparation for communicating effectively with patients (Evans, 2008), the learning benefits of verbal discussions and oral presentations by students in anatomy education (Lake, 2001;Philip et al, 2008), and the need to identify and consider different learning styles of clinical students (Lujan and DiCarlo, 2006).…”
Section: Context For This Studymentioning
confidence: 97%